International donors in democratic South Africa: a comparative-case study - Groeblinghoff, Barbara (My University, 1996)
International donor organisations have been in a somewhat extraordinary position in South Africa until recently; since the previous dispensation lacked national as well as international legitimacy, donors were unwilling to channel their funds through government. This meant that donors could on the whole set their own priorities as to where and how and by whom their money was to be spent. The purpose of this research is to assist in making some specific donor organisations (German political Foundations) more transparent on the one hand, and to contribute more generally, albeit in a small way, in making available information on donors to policy makers. The research found that the gravest concern on the part of recipient organisations was the perceived lack of accountability and transparency on the part of the donors.
A research report submitted to the Faculty of Management, University of the Witwatersrand, in partial fulfilment of the requirements for the degree of Master of Management (in the field of Public and Development Management).
Keywords: ECONOMIC ASSISTANCE--SOUTH AFRICA.; ECONOMIC DEVELOPMENT PROJECTS--SOUTH AFRICA.; NON-GOVERNMENTAL ORGANIZATIONS--SOUTH AFRICA--FINANCE.